2018
DOI: 10.1139/cjas-2017-0038
|View full text |Cite
|
Sign up to set email alerts
|

Producer perceptions of manual and automated milk feeding systems for dairy calves in Canada

Abstract: As part of a cross-sectional survey, Canadian dairy producers were asked a set of questions to (1) determine factors that influenced them to continue using manual milk feeding (MMF) systems or to switch to automated milk feeding (AMF) and (2) investigate producers’ perceived advantages and disadvantages regarding both feeding systems. A total of 670 responses were received. Among respondents, 16% used AMF and 84% used MMF. The four most frequent factors that producers reported as important in motivating them t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Consequently, alternatives such as automation of various tasks e.g. calf feeding, need to be considered as their increased use is perceived as an efficiency investment for farmers (Medrano-Galarza et al, 2017). Traditionally, Irish dairy farms manually feed group-housed calves through multi-teat feeders (Barry et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, alternatives such as automation of various tasks e.g. calf feeding, need to be considered as their increased use is perceived as an efficiency investment for farmers (Medrano-Galarza et al, 2017). Traditionally, Irish dairy farms manually feed group-housed calves through multi-teat feeders (Barry et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Medrano-Galarza et al (2017a) reported that 36% of 670 dairy farms that participated in a survey on calf rearing practices across Canada housed calves in groups and 16% fed milk through AMF machines. The adoption of AMF is increasing steadily among producers (Medrano-Galarza et al, 2017a) as a way to improve working conditions and reduce physical labor while facilitating feeding high volumes of milk in multiple portions throughout the day to group-housed calves (Medrano-Galarza et al, 2017b). Nevertheless, some producers attribute difficulties with AMF (i.e., perceived high morbidity and mortality) to the feeders themselves and the type of housing (Endres, 2013), with some producers switching back to individual housing and feeding (Medrano-Galarza et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some producers attribute difficulties with AMF (i.e., perceived high morbidity and mortality) to the feeders themselves and the type of housing (Endres, 2013), with some producers switching back to individual housing and feeding (Medrano-Galarza et al, 2017a). Producers perceive individual housing and individual feeding as a way to reduce disease transmission (Medrano-Galarza et al, 2017b) by limiting direct contact between calves, which has also been recommended by veterinarians (Callan and Garry, 2002;Stull and Reynolds, 2008). Observational studies in Sweden have shown the risk of bovine respiratory disease (BRD) to be significantly higher for AMF-fed calves housed in groups of 6 to 30 calves/pen compared with manually fed calves housed individually (Lundborg et al, 2003(Lundborg et al, , 2005 or in groups of 3 to 8 calves/pen (Lundborg et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is growing interest in feeding higher amounts of milk to achieve increased weight gains before weaning; with appropriate gradual weaning methods to encourage early solid feed intake, such as an initial early milk reduction (e.g., ( Rosenberger et al, 2017 ) or weaning calves based on their ability to consume solid feed ( de Passillé and Rushen, 2016 ), calves can successfully be raised on a higher plane of nutrition. Best practices such as feeding high amounts of milk with a nipple bottle have been cited by producers as requiring added labor and thus added cost to the operation ( Medrano-Galarza et al, 2017 ); this is likely why milk feeding remains restricted in many countries. Consequently, bucket feeding is often used because they are fast and easy to clean ( Medrano-Galarza et al, 2017 ); however, this practice is associated with higher nonnutritive oral behaviors such as sucking on fixtures ( Horvath and Miller-Cushon, 2017 ), likely due to the calf’s inability to satisfy its natural motivation to suckle from a teat ( Jensen, 2003 ).…”
Section: Conventional Calf-raising Practices Compared To In Naturementioning
confidence: 99%
“…Best practices such as feeding high amounts of milk with a nipple bottle have been cited by producers as requiring added labor and thus added cost to the operation ( Medrano-Galarza et al, 2017 ); this is likely why milk feeding remains restricted in many countries. Consequently, bucket feeding is often used because they are fast and easy to clean ( Medrano-Galarza et al, 2017 ); however, this practice is associated with higher nonnutritive oral behaviors such as sucking on fixtures ( Horvath and Miller-Cushon, 2017 ), likely due to the calf’s inability to satisfy its natural motivation to suckle from a teat ( Jensen, 2003 ). Costa et al (2016a) suggested that such abnormal oral behaviors can be rectified when limited milk allowances, bucket feeding, and abrupt weaning methods are corrected.…”
Section: Conventional Calf-raising Practices Compared To In Naturementioning
confidence: 99%